Cartografia do interior bahiano. Uma análise de três mapas anônimos do século XVIII - Grégoire van Havre (Confins)
The colonial cartography of the territory of Bahia is limited by the availability of sources. Too few documents allow us to present the space of the Captaincy, and the reports of the period lack information about distances. In this paper, we analyze three documents broadly dated from the XVIIIth century. We show how it is possible to point their origin to a more precise timeframe. Based on this, we then realize a complete spatial analysis, revealing a peopling process more complex than what has generally been depicted in the literature. These maps indicate a movement beyond the main classical communication axes, the first to Minas Gerais and the second to the State of Maranhão-Grão-Pará.